Diel patterns of oceanic dimethylsulfide (DMS) cycling: Microbial and physical drivers. Issue 3 (2nd July 2013) - Galí, Martí; Simó, Rafel; Vila‐Costa, Maria; Ruiz‐González, Clara; Gasol, Josep M.; Matrai, Patricia
Abstract [1] Dimethylsulfide (DMS) is a biogenic gas with potential climatic effects, and its marine emission depends on the interplay between microbial activity and physical forcing in the oceanic upper mixed layer. We investigated the diel cycling patterns of DMS and its precursor dimethylsulfoniopropionate (DMSP) in four experiments (28 to 48 h long) performed in mesotrophic to ultraoligotrophic Mediterranean and Sargasso Sea waters. Samples taken every 4 or 6 h were analyzed for dimethylated sulfur pools and incubated to measure DMS and DMSP cycling rates, as well as primary and bacterial production. In all four experiments, DMS budgets showed pronounced day versus night variability. In the three summer experiments, gross community DMS production (GPDMS) increased by twofold to threefold from nighttime to daytime, peaking 0–4 h after solar noon. This excess GPDMS was balanced by higher photochemical and microbial sinks during the day, effectively buffering DMS concentrations. In the only winter experiment, GPDMS exhibited opposed temporal dynamics and peaked at nighttime in parallel to total DMSP consumption. Community DMSP to DMS conversion yields were generally <10% throughout the winter experiment and at night in summer, and increased to >15% (even >50%) during the day in summer, presumably due to phytoplankton radiative stress. Our data suggest that (1) diel variability should be taken into account in process studies, diagnostic, and prognostic models of DMS cycling and (2) the community DMS yield is a key variable that defines characteristic DMS cycling regimes.